Necessary and Sufficient Conditions for Factor Price Equalization. - Blackorby, C; Schworm, W; Venables, A (1993)
Although models with factor price equalization are used frequently in both theoretical and applied research in international economics, only sufficient conditions for factor price equalization have been presented in the literature. In this paper, the authors present necessary and sufficient conditions for factor price equalization under quite general assumptions about the technologies of different countries. The necessary and sufficient conditions they derive are consistent with joint production, decreasing returns to scale, and substantive differences in the technologies and endowments of different countries. The authors' results enable them to reconcile the classical approach and the integrated equilibrium approach to factor price equalization.